To fill in the missing step in the proof of the equivalence \( 12a + 10 + a = 10 + a + 12a \) using the Commutative Property, we need a step that rearranges the terms in the expression \( 12a + 10 + a \).
The correct missing step is:
Step 1: 10 + 12a + a = 10 + a + 12a
This uses the Commutative Property, which allows us to rearrange the terms in an expression.
The final sequence would look like this:
Step 1: 10 + 12a + a = 10 + a + 12a
Step 2: 10 + 13a = 10 + 13a
Step 3: The expressions are equivalent because they both equal the same value.
The first response option, 12a+10=10+12a, is also a valid use of the Commutative Property, but it doesn't lead directly to rearranging to form the step needed in this proof sequence. The best choice that leads to the sequence in the proof is:
10 + 12a + a = 10 + a + 12a.